A genome‐wide search for local adaptation in a terrestrial‐breeding frog reveals vulnerability to climate change - Cummins, Deanne; Kennington, W. Jason; Rudin‐Bitterli, Tabitha; Mitchell, Nicola J. (Global change biology, 2019)
Terrestrial‐breeding amphibians are likely to be vulnerable to warming and drying climates, as their embryos require consistent moisture for successful development. Adaptation to environmental change will depend on sufficient genetic variation existing within or between connected populations. Here, we use Single Nucleotide Polymorphism (SNP) data to investigate genome‐wide patterns in genetic diversity, gene flow and local adaptation in a terrestrial‐breeding frog (Pseudophryne guentheri) subject to a rapidly drying climate and recent habitat fragmentation. The species was sampled across 12 central and range‐edge populations (192 samples), and strong genetic structure was apparent, as were high inbreeding coefficients. Populations showed differences in genetic diversity, and one population lost significant genetic diversity in a decade. More than 500 SNP loci were putatively under directional selection, and 413 of these loci were correlated with environmental variables such as temperature, rainfall, evaporation and soil moisture. One locus showed homology to a gene involved in the activation of maturation in Xenopus oocytes, which may facilitate rapid development of embryos in drier climates. The low genetic diversity, strong population structuring and presence of local adaptation revealed in this study shows why management strategies such as targeted gene flow may be necessary to assist isolated populations to adapt to future climates. Terrestrial‐breeding frogs are likely to be vulnerable to warming and drying climates, as their embryos require consistent moisture for successful development. We generated Single Nucleotide Polymorphism data to investigate genome‐wide patterns in genetic diversity, gene flow and local adaptation in a terrestrial‐breeding frog (Pseudophryne guentheri) subject to a rapidly drying climate and recent habitat fragmentation. Our analyses revealed strong population genetic structure, potential inbreeding and a decline in genetic diversity over 10 years in one population. We also provide strong molecular evidence of local adaptation to environmental variables such as rainfall, evaporation and soil moisture.